Colour discrimination ellipses in choroideremia - Seitz, IP; Jolly, JK; Fischer, MD; Simunovic, MP (Springer, 2018)
Purpose The purpose of this study was to characterise alterations in colour discrimination in a cohort of patients with choroideremia prior to gene therapy, using a test previously validated for use in patients with retinal dystrophies. Methods We tested 20 eyes of 10 patients with a diagnosis of choroideremia and an age-matched cohort of 10 eyes of 10 normal controls using the "Cambridge Colour Test" (CCT), in which subjects are required to distinguish the gap in a C presented in one of 4 orientations in a Stilling-type array. Colour discrimination was probed along eight axes in the CIE L*u*v* colour space, and the resulting data were plotted in the CIE 1976 chromaticity diagram and fitted with least-squares ellipses. Subsequently, we estimated the achromatic area for each subject by calculating the area of the resultant discrimination ellipse and calculated sensitivity thresholds along relevant colour confusion axes. Results Colour discrimination—as quantified by log10 of the ellipse area expressed in square 1/1000th^2 units in CIE 1976 — was 2.26 (range 1.82 to 2.67) for normal subjects and 3.85 (range 2.35 to 5.41) for choroideremia patients. There was a statistically significant correlation between both achromatic area and red-green colour discrimination at the CCT and BCVA, and to a lesser degree between blue colour discrimination at the CCTand BCVA. The majority of ellipses in choroideremia were aligned close to the tritan axis, and loss of sensitivity was significantly larger in the tritan direction than in the red-green. Conclusions The majority of our patients demonstrated greater loss in tritan discrimination than in red-green colour discrimination using the CCT. There was a significant correlation between achromatic area and BCVA. In keeping with our current understanding of the machinery of colour vision, there was a significant correlation between BCVA and colour discrimination thresholds, which was stronger for red-green colour discrimination, than for tritan colour discrimination.We propose that this and similar tests of colour discrimination may prove to be suitable tools for assessing functional outcomes in gene therapy trials for choroideremia.